Asymmetric Inverse-Electron-Demand Diels–Alder Reactions of 2-Pyrones by Lewis Acid Catalysis - Si, Xu-Ge; Zhang, Zhi-Mao; Cai, Quan (Synlett, 2021)
Diels–Alder reactions of 2-pyrones with alkenes can provide highly functionalized [2,2,2]-bicyclic lactones under mild reaction conditions. Synthetic utilizations of these reactions have been well demonstrated in natural-product synthesis. Although several catalytic asymmetric strategies have been realized, current research in this area is still largely underdeveloped. Recent advances in enantioselective inverse-electron-demand Diels–Alder reactions with Lewis acid catalysis are reviewed.1 Introduction2 State of the Art of Enantioselective Diels–Alder Reactions of 2-Pyrones by Lewis Acid Catalysis3 Enantioselective Synthesis of Arene cis-Dihydrodiols by Diels–Alder/Retro-Diels–Alder Reactions of 2-Pyrones4 Enantioselective Synthesis of cis-Decalin Derivatives by Diels–Alder Reactions of 2-Pyrones5 Conclusions
Keywords: pyrones; asymmetric catalysis; Diels–Alder reactions; Lewis acid catalysis; natural product synthesis